CHALLENGES OF WEB-BASED PARTICIPATORY LEARNING - Marzano, Gilberto; Ochoa-Siguencia, Luis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
In the last decade, the spread of the Internet has increased the importance of informal learning, since any sort of knowledge, both popular and scientific, can be found on the Internet in multifarious forms, e.g. online newspapers, books and e-books, scientific journals, blogs, forums, images, videos, etc.This paper analyses some challenges of Web-based learning, and briefly reports on an experience of computer-supported collaborative learning that is based on a social learning approach.